2010
DOI: 10.1128/aac.00802-10
|View full text |Cite
|
Sign up to set email alerts
|

Improved Detection of Mutated Human Cytomegalovirus UL97 by Pyrosequencing

Abstract: Ganciclovir (GCV) resistance frequently occurs upon prolonged treatment of ongoing active human cytomegalovirus (HCMV) infection in individuals with immature or compromised immune functions (e.g., recipients of solid-organ and hematopoietic stem cell transplants). Using pyrosequencing (PSQ), we established fast and sensitive detection of GCV resistance-associated mutations occurring in the HCMV open reading frame UL97. These mutations have been repeatedly associated with clinical treatment failure. We designed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…had been defined for four PSQ assays (15). In the present study, the detection limits of 19 assays were Ͻ6%, but those of 10 assays were Ͼ6% and those of 3 assays were Ͼ10%.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…had been defined for four PSQ assays (15). In the present study, the detection limits of 19 assays were Ͻ6%, but those of 10 assays were Ͼ6% and those of 3 assays were Ͼ10%.…”
Section: Resultsmentioning
confidence: 81%
“…In this study of VZV variants, mixed alleles with small wt minorities were detected with a high sensitivity by PSQ. While CTSQ usually does not detect allele or mutant minorities present at levels below 20% in mixed alleles (2,15), most PSQ assays detect them with a detection limit well below 10% (15; this study). Furthermore, alleles can be quantified by PSQ, in contrast to CTSQ.…”
Section: Vol 18 2011 Molecular Analysis Of Vzv From Vaccines and Vamentioning
confidence: 99%
“…20,21 PSQ has been already used to study several viral mutations known to induce drug resistance and very recently, in this system it has been used for qualitative analysis of CMV-resistance. [22][23][24][25][26] …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggested that mixed cytomegalovirus populations composed of wild-type and GCV-resistant strains occurred in immunosuppressed patients following GCV treatment (29,30). Thus, further pyrosequencing analyses may be needed to determine the precise incidence of the emergence of GCV-resistant HHV-6B strains in immunocompromised patients following GCV administration.…”
Section: Discussionmentioning
confidence: 99%